Comparative Efficacy of High Dose Dexamethasone vs Low Dose Methylprednisoslone Therapy in Covid Pneumonia - Syed Anees Ahmed Gardezi, Najmusaqib Khan Niazi, S. Haider Tirmizi, Iffat Rafique, Rabia Sadiq, Muneeb Ur Rehman, Talha Laique (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Around one and half years ago in the December of 2019 a flu like disease emerged in the city Wuhan located in China. This was termed by WHO as a global pandemic due to its rapid widespread. Aim: To compare the efficacy of high dose dexamethasone (8 mgx tds) vs low dose methylprednisoslone (100 mgx bd) therapy for two weeks, in resolution of acute inflammatory markers in patients with covid pneumonia. Study Design: Quasi experimental study. Methodology: Patients (n=72) with an age range of 18-70 years with Covid 19 PCR positive having Covid associated pneumonia were enrolled. Group 1 containing 36 patients receiving high dose dexamethasone (8 mgx TDS) and group 2 with 36 participants receiving low dose methylprednisolone (100 mgx BD). Inflammatory markers (CRP, ESR and Ferritin) were recorded on Day 1 (T1) on day 7 (T2) and day 14 (T3). Patients who required ventillatory support and those who died was also recorded.All this information was recorded on Performa. Data was analyzed using SPSS version 26. Results: Mean age of the patients was 50.11±11.7 years. When we compared the inflammatory markers among group 1 and group 2 at T1, T2 and T3 no statistically significant difference was obtained. Conclusion: It was concluded that high dose dexamethasone and low dose methylprednisoslone therapy for two weeks were equally effective in resolution of acute inflammatory markers in patients with covid pneumonia.